Controllable resonance frequency in Ni/Pb(Zr, Ti)O3/FeCo cylindrical composites. (June 2014) - Hong, H.; Bi, K.; Wu, W.; Chen, F. G.
Abstract : Magnetoelectric (ME) Ni/Pb(Zr, Ti)O3 /FeCo cylindrical layered composites with a negative magnetostrictive/piezoelectric/positive magnetostrictive structure have been prepared by electroless deposition. The magnetostrictive layers are in direct contact with the piezoelectric layer. The ME effect was measured by applying both constant and alternating magnetic fields parallel and perpendicular to the cylinder's axis direction. The ME voltage coefficient increases, and the resonance frequency decreases as the cylinder diameter increases. The experimental resonance frequency is very close to the calculated ones. This characteristic of resonance frequency can be applied to design a kind of ME composites with the controllable resonance ME coupling.